Morphological and genetic variability of local Echinochloa accessions and the link with herbicide sensitivity. (21st January 2016) - Claerhout, S; Dewaele, K; De Riek, J; Reheul, D; De Cauwer, B
Summary: Echinochloa crus‐galli and Echinochloa muricata are common weeds in Belgian maize fields. Both species are morphologically difficult to distinguish and exhibit high morphological variability. Their response to herbicides varies from field to field. This study investigated whether the considerable morphological polymorphism found among Belgian Echinochloa accessions has a genetic background and whether it is consistently associated with differences in sensitivity to maize herbicides. For this purpose, accessions of E. crus‐galli and E. muricata were compared for morphological and genetic resemblance and tested for herbicide sensitivity. All accessions were planted in the field to examine the morphological traits. A cluster analysis was conducted to assess them for morphological diversity. DNA of leaf material was used for amplified fragment length polymorphism analysis to cluster the accessions genetically. Dose–response pot experiments were conducted in the glasshouse to assess the effectiveness of an acetolactate synthase (nicosulfuron), acetyl‐CoA carboxylase (cycloxydim) and 4‐hydroxyphenyl phosphate dioxygenase (topramezone) inhibiting herbicide. The genetic and morphological clusters were compared with the effective doses obtained from the dose–response bioassays. Morphological variation significantly correlated with genetic variation, but the relation with herbicide sensitivity was weak. Spikelet size and biomass characteristics are reliable discriminating characteristics for (sub)species classification. Intraspecies identification does not seem essential for optimisation of chemical control of E. crus‐galli and E. muricata in the field.